Relative Efficacies of Individual Psychology and Cognitive Behavioural Therapy in the Reduction of Suicide Ideation among Undergraduate Students in the University of Cape Coast, Ghana - Adom-Mensah, Benedicta Ama; Omotosho, Joshua A.; Bediako, Sylvia Eyiah; Kwarteng-Nantwi, Eugene (Journal of Advanced Psychology, 2023)
Purpose: The purpose of the study was to find out the relative efficacies of Individual Psychology (IP) and Cognitive Behavioural Therapy (CBT) in the reduction of suicide ideation among undergraduate students of University of Cape Coast, in the Central Region, Ghana. Methodology: It was a quantitative study using the quasi-experimental research design, specifically, the pre-test, post-test and control group design. A total of 30 undergraduate students from four colleges of the University were non-randomly assigned to two treatment groups (IP and CBT) and one control group. The Beck Scale for Suicide Ideation was used for data collection. Both the descriptive (frequency and percentage) and inferential (independent samples t-test) statistics were used to analyse the data at .05 alpha level. Findings: The results revealed that both therapies are effective in reducing suicide ideation among undergraduate students, with CBT being slightly more effective than IP. Unique Contribution to Theory, Policy and Practice: It was recommended that screening for suicide ideation, spearheaded by the Counselling Centre of the University, should be carried out on a regular basis among students of the University. This is with a view to achieving a drastic reduction in suicide ideation, and by implication, suicide itself